Persepsi dan Respon Pelaku UMKM terhadap Penerapan QRIS sebagai Sistem Pembayaran Digital di Desa Serbananti - Putri Andini; Nadya Nadya; Sunan Agung Nugroho; Nurul Huda Prasetya (Lembaga Pengembangan Kinerja Dosen, 2026)
The digitalization of payment systems has become an important breakthrough in supporting the efficiency of financial transactions, including in the micro, small, and medium enterprises (MSMEs) sector. The Quick Response Code Indonesian Standard (QRIS) was introduced as a digital payment instrument expected to enhance convenience, security, and accessibility in transactions. This study aims to explore the perceptions and responses of MSME actors in Serbananti Village toward the implementation of QRIS as a digital payment system. The research employed a qualitative approach through in-depth interviews and observations involving five MSMEs that have received QRIS facilities. The findings indicate that some MSME actors hold positive perceptions of QRIS, viewing it as practical, modern, and aligned with current consumer payment trends. However, challenges were also identified, such as limited digital literacy, concerns about additional costs, and consumers’ preference for cash transactions. Therefore, it can be concluded that the implementation of QRIS in Serbananti Village still requires intensive socialization and technical assistance to enable MSMEs to maximize the benefits of this digital payment system.